Public Health Surveillance in the Dialysis Setting: Opportunities and Challenges for Using Electronic Health Records. Issue 4 (31st May 2013) - Wise, Matthew E.; Lovell, Chris
Abstract The US Centers for Disease Control and Prevention has conducted public health surveillance for healthcare‐associated infections (HAIs) in dialysis facilities since the 1970s, evolving from facility‐level surveys to patient‐level surveillance systems. The Centers for Medicare and Medicaid Services (CMS) recently implemented incentives for all end‐stage renal disease (ESRD) facilities to monitor and report patient‐level quality indicators to the Centers for Disease Control and Prevention's (CDC's) National Healthcare Safety Network (NHSN) in accordance with the NHSN Dialysis Event Protocol. These CMS incentives have led to a rapid increase in dialysis facility NHSN enrollment during 2012. Ongoing challenges to HAI surveillance in this setting include variability in the surveillance process, assurance of data quality, and staff time and resource requirements. Use of existing electronic health records (EHR), especially in conjunction with detection algorithms, has increasingly been shown to produce valid and reliable estimates of HAI frequency in acute care hospitals. Given the large number of dialysis facilities that are now beginning to conduct surveillance using NHSN, the typical lack of dedicated infection prevention personnel in those facilities, and the widespread use of EHR in large dialysis provider organizations, the use of EHR will probably become a cornerstone of surveillance in these settings. Implemented properly, the use of EHR to support public health surveillance has enormous potential to focus and strengthen infection prevention activities in dialysis facilities. Systematic, ongoing validation efforts will be vital to ensure that reported data are accurate, permit valid comparisons of facility performance, and effectively support improved outcomes for dialysis patients.